2005
DOI: 10.1038/nature03863
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the naked grains of maize

Abstract: The most critical step in maize domestication (Zea mays ssp. mays) was the liberation of the kernel from the hardened, protective casing that envelops the kernel in the maize progenitor, teosinte 1 . This evolutionary step exposed the kernel on the surface of the ear such that it could be readily utilized as a food source by humans. Here, we show that this key event in maize domestication is controlled by a single gene (teosinte glume architecture; tga1) belonging to the SBP-domain family 2 of transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
413
4
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 548 publications
(453 citation statements)
references
References 23 publications
12
413
4
1
Order By: Relevance
“…Association between a few mutations/genes and dramatic phenotypic changes or fitness improvement have been reported in prokaryotes, eukaryotes and viruses (Taubenberger et al, 2005;Wang et al, 2005;Zeyl 2005;Herring et al, 2006;Schoustra et al, 2009). Results from this study indicated the linkage between significantly increased salt tolerance and a few mutations.…”
Section: Discussionmentioning
confidence: 52%
“…Association between a few mutations/genes and dramatic phenotypic changes or fitness improvement have been reported in prokaryotes, eukaryotes and viruses (Taubenberger et al, 2005;Wang et al, 2005;Zeyl 2005;Herring et al, 2006;Schoustra et al, 2009). Results from this study indicated the linkage between significantly increased salt tolerance and a few mutations.…”
Section: Discussionmentioning
confidence: 52%
“…Evidence of directional selection has been found in the upstream cis-regulatory regions of noncoding region of tb1, suggesting adaptive changes in expression of this gene (Clark et al, 2006). Regulatory changes have also been implicated in the evolution of naked grains in maize (Wang et al, 2005) and in the loss of seed shattering in rice (Konishi et al, 2006).…”
Section: Introductionmentioning
confidence: 94%
“…We found significant variation with flow rate, suggesting a mass transfer limitation (data not shown). Varying concentrations of recombinant protein (5,10,15,20,25,30, and 50 nM) were injected at the higher flow rate (75 ”L/min). The SPR response data were then fit to various models using BIAevaluation 3.0 software (Biacore).…”
Section: Identification Of a Consensus Binding Site For The Atspl14 Smentioning
confidence: 99%
“…To date, only a few functions for SBP domain proteins have been reported, perhaps due to genetic redundancy of closely related family members. In all cases, SBP domain proteins have been implicated in various aspects of plant growth and development, including metal sensing in algae and directing development of leaves, embryos, and floral organs in higher plants (9,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Some of these SBP do-main proteins may also be posttranscriptionally regulated by noncoding microRNAs to control their spatial and temporal expression (23)(24)(25).…”
mentioning
confidence: 99%